2017
DOI: 10.1136/thoraxjnl-2016-209553
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory viruses in healthy infants and infants with cystic fibrosis: a prospective cohort study

Abstract: Viral detection is not more frequent in infants with CF and respiratory symptoms during viral detection occur even less often than in healthy controls. It is likely an interplay of different factors such as local epithelial properties and immunological mechanisms that contribute to our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
(10 reference statements)
3
8
0
Order By: Relevance
“…Prior studies in healthy infants show a wide range of viral positivity, anywhere from 23% [ 23 ] to 69% [ 19 ]. Comparing to studies examining viruses in the first year of life [ 19 , 20 , 22 , 24 ], we found comparable findings as in those studies viral positivity ranged from 27% [ 24 ] to 69% [ 19 ] in healthy infants. Our rates of detection in home versus clinic collected samples were not significantly different.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Prior studies in healthy infants show a wide range of viral positivity, anywhere from 23% [ 23 ] to 69% [ 19 ]. Comparing to studies examining viruses in the first year of life [ 19 , 20 , 22 , 24 ], we found comparable findings as in those studies viral positivity ranged from 27% [ 24 ] to 69% [ 19 ] in healthy infants. Our rates of detection in home versus clinic collected samples were not significantly different.…”
Section: Discussionsupporting
confidence: 86%
“…Lastly, we did not have a control group due to the nature of the study protocol which included bronchoscopy and infant lung function testing, sedated procedures that would not be electively performed on healthy infants. However, there are multiple epidemiologic studies of viral infections in healthy infants to which our prevalence results are comparable [ 19 , 20 , 22 , 24 ].…”
Section: Discussionmentioning
confidence: 80%
“…The prevalence of respiratory virus in this study was 35.7%. In agreement with previous studies, picornaviridae viruses were the most frequently detected viruses, regardless of age [ 4 9 , 12 , 20 , 21 ]. RSV was the second most frequent virus, and had the lowest hospital admission rate, even though it has been suggested that CF patients could be at risk for more severe infection by this agent [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…does not impact airway neutrophil CD63 expression at the time of the measurement, we cannot exclude potential impact of prior infections, or low-level presence of atypical organisms (24). Viral infections may also be at play, although a recent study suggested that children with CF do not suffer more frequent viral infections or increased inflammatory responses on viral infections than children without CF (64).…”
Section: Discussionmentioning
confidence: 89%